SISTEM PENDUKUNG KEPUTUSAN PENENTUAN SISWA TELADAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) STUDI KASUS : SD BHAKTI YKKP - Surono, Galih; Pusparini, Nur Nawaningtyas (ISTEK WIDURI, 2020)
Exemplary students are students of noble and accomplished character. Exemplary student assessments in schools are essential to motivate students to be better. Sekolah Bhakti YKKP is a school that plans to conduct an exemplary student assessment. The exemplary student assessment in SD Bhakti is taken from 8 aspects of assessment, namely: Average player ratings value, moral, discipline, attendance, point of offense, extracurricular activities of the race and book lover. A lot of data and different judging aspects become constraints in the assessment process, to solve this problem. The purpose of this research is to create a decision support system (SPK) as a solution to help schools in determining exemplary students. SPK applied is using Simple Additive Weighting (SAW) method, because this method can calculate various values based on predefined criteria and weights. After the calculation process is complete, the calculation result of the SAW method can be used to determine the student model based on the best class rating. Based on the results of the test using the PHP programming language and two methods of testing Black Box with an average percentage of 86% and testing Delone and McLean Model with an average percentage of 88%.